22.4: Multi‐stable LCD with Dual‐frequency Reverse‐mode Polymer Stabilized Cholesteric Texture. Issue 1 (1st July 2013) - Peli‐Smith, Andrew M.; Wu, Cheng‐Che; Wang, Che‐Syuan; Chiu, Tien‐Lung; Lee, Jiunn‐Yih; Lee, Jiun‐Haw
Abstract: In this paper, we have demonstrated a LCD which can be stabilized with multiple states (tansmittance 10–90%) at 0 bias which can maintain for over 2 weeks by using reverse mode polymer stabilized texture with dual frequency LC materials.